Die teologiese en morele regverdiging van apartheid en 'n status confessionis - P. J. Strauss (Acta Theologica)
Both the World Alliance of Reformed Churches (WARC) and the — then — Reformed Ecumenical Synod (RES) eventually declared a status confessionis against the theological and moral justification of apartheid. In this process the Afrikaans Reformed Churches came under serious fire. The questions arising from this are: When is a status confessionis a relevant option for the church? How did both the WARC and the RES handle the matter and were there any differences in their approach due to their differences as ecumenical bodies? The conclusion is that the WARC followed certain anti-apartheid elements in the younger Dutch Reformed Churches uncritically while the RES took a more independent stand. A further problem was that the WARC did not qualify the apartheid it was speaking out against. That complicated dialogue with the Dutch Reformed Church. Both organizations, however, showed clear indications of an awareness that they tried to consider the basic conditions for a status confessionis.